The Role of Islamic Religious Education Teachers in Character Education: A Qualitative Study at Mutiara Hikmah Vocational High School (SMK) - Nasrullah, Agus; Salam DZ, Abdus; Haedari, Amin; Karim, Abdul (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to investigate the critical role of Islamic Religious Education (PAI) teachers in character education at Mutiara Hikmah Vocational High School (SMK) during the 2022/2023 academic year. Within the context of globalization, which has significantly influenced moral values in Indonesia, this study seeks to address the noticeable decline in student discipline and morality. By focusing on the contributions of PAI teachers, the study aims to highlight effective strategies for enhancing student character development, shaping individuals who are intelligent, independent, and morally upright. Design/methods/approach – A descriptive qualitative methodology was employed to gain an in-depth understanding of the dynamics at Mutiara Hikmah Vocational High School (SMK). This research involved participatory observation, semi-structured interviews, and document analysis. Data were collected from July 1 to August 20, 2023, through daily observations, interviews with PAI teachers, the principal, and other teachers, as well as analysis of school documents such as academic records and activity reports. Thematic analysis was used to identify key themes and patterns related to character education. Findings – The findings indicate that PAI teachers play a crucial role in instilling discipline and moral values through classroom instruction and extracurricular activities such as congregational prayers and Qur'an literacy sessions. However, challenges such as inconsistent disciplinary standards and limited parental involvement were noted. The study also highlights the need for improved facilities and ongoing training for teachers to support character education. Research implications – The results suggest that a holistic approach involving collaboration among teachers, parents, and the community is essential for effective character education. Policymakers and educators should prioritize the development of comprehensive character education programs that integrate cognitive, affective, and psychomotor aspects. Future research should explore the long-term impacts of such programs and the specific contributions of various extracurricular activities.